The Stress-Strain State Computer Modelling of Reinforced Masonry Under Local Loading - Pinchuk, Nataliia; Fenko, Oleksiy; Kyrychenko, Volodymyr (International Journal of Engineering and Technology, 2018)
Reinforced masonry elements stress-strain state modelling allows to define places in which stresses and strains are maximum. It is necessary to pay special attention to these places during experimental investigation. Accepted models of structures are adequate and corresponded to real constructions. Using computer modelling by the finite element method, the finite element size influence on the calculation accuracy is determined. The necessary resources of a personal computer to create and calculate such a model are sufficient and suitable for studying modelled structures stress-strain state. Good convergence of the deformations obtained from the resistive-strain sensors during the experimental investigations and according to the numerical modelling results is received.Â Â